Comparison of four mobile, non‐invasive diagnostic techniques for differentiating glass types in historical leaded windows: MA‐XRF, UV–Vis–NIR, Raman spectroscopy and IRT. (24th August 2020) - Cagno, Simone; Van der Snickt, Geert; Legrand, Stijn; Caen, Joost; Patin, Mathilde; Meulebroeck, Wendy; Dirkx, Yarince; Hillen, Michaël; Steenackers, Gunther; Rousaki, Anastasia; Vandenabeele, Peter; Janssens, Koen
Abstract : This paper critically compares the performance of four non‐invasive techniques that match the accuracy, flexibility, time‐efficiency, and transportability required for in situ characterization of leaded glass windows: macroscopic X‐ray fluorescence imaging (MA‐XRF), UV–Vis–NIR, Raman spectroscopy, and infrared thermography (IRT). In order to compare the techniques on equal grounds, all techniques were tested independently of each other by separate research groups on the same historical leaded window tentatively dated to the 17th century, without prior knowledge. The aim was to assess the ability of these techniques to document the conservation history of the window by classifying and grouping the colorless glass panes, based on differences in composition. IRT, MA‐XRF and UV–Vis–NIR spectroscopy positively distinguished at least two glass groups, with MA‐XRF providing the most detailed chemical information. In particular, based on the ratio between the network modifier (K) and network stabilizer (Ca) and on the level of colorants and decolorizers (Fe, Mn, As), the number of plausible glass families could be strongly reduced. In addition, UV–Vis–NIR detected cobalt at ppm level and gave more specific information on the chromophore Fe 2+ /Fe 3+ ratio. Raman spectroscopy was hampered by fluorescence caused by the metal ions of the decolorizer in most of the panes, but nevertheless identified one group as HLLA.